Disease burden and cost of hidradenitis suppurativa: a retrospective examination of US administrative claims data - Jessica Marvel; Anna Vlahiotis; Amy Sainski-Nguyen; Tina Willson; Alexandra Kimball (BMJ Open)
Objectives Hidradenitis suppurativa (HS) causes substantial morbidity and quality-of-life impairment. We examined demographic/clinical characteristics of patients with HS and treatment patterns, prevalence and healthcare resource utilisation/expenditures related to HS in the real-world.Design Retrospective claims data of MarketScan Commercial, Medicare Supplemental and Medicaid databases (2009–2014).Setting USA.Participants Patients aged ≥12 years with ≥3 non-diagnostic outpatient or inpatient claims with an HS diagnosis code and ≥12 months continuous enrolment with medical and pharmacy benefits before (preindex) and after (postindex) the earliest diagnosis of HS (index) were included.Results There were 11 325 Commercial/Medicare patients (mean age 37.4 years) and 5164 Medicaid patients (mean age 28.3 years). HS was more common in Medicaid than Commercial/Medicare patients (0.301% and 0.098%, respectively, in 2014). Cellulitis and psychiatric disorders were the most common comorbidities and oral antibiotics and narcotics were the most frequently prescribed drugs preindex, with ≥10% increase postindex in both populations. HS-related inpatient costs decreased while outpatient costs increased from preindex to postindex. Medicaid patients had several risk factors that may be associated with poor outcomes (eg, high rates of prescription pain medication use, comorbidities, drug discontinuation/interruption/holiday, emergency department (ED) visits and hospitalisation).Conclusions Commercial/Medicare and Medicaid HS beneficiaries experience high comorbidity burden but use different treatment modalities to manage HS. Results suggest a substantial unmet need exists among this patient population, with Medicaid patients experiencing a particularly high burden of disease and expensive healthcare resource utilisation.